FINANCIAL ANALYSIS OF DUCKWEED USE (Lemna sp.) FERMENTED BAKER'S YEAST (Saccharomyces cerevisiae) AS A CONSTITUENT INGREDIENT IN BROILER CHICKEN RATIONS - I M. Y., Artawan; Kayana, I G. N.; Mahardika, I G. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of the use of fermented duckweed on broiler business finances. This research was conducted in Banjar Cabe, Darmasaba Village, Abiansemal District, Badung Regency, Bali for eight weeks. This study used a Complete Randomized Design Submitted Date: June 7, 2023 Accepted Date: September 3, 2023 Submitted Date: November 12, 2020 Accepted Date: January 3, 2021 Editor-Reviewer Article: Eny Puspani & A.A. Pt. Putra Wibawa Editor-Reviewer Article : Ni Putu Mariani & Dsk. Pt. Mas Ari Candrawati Artawan, I M. Y., Peternakan Tropika Vol. 12 No. 2 Th. 2024: 64 – 79 Page 65 (RAL) with four treatments, four repeats, and 16 experimental units. Finisher phase broilers in the P0 treatment were given feed in the form of 100% BR2 commercial rations, while in the P1, P2, and P3 treatments were given BR2 commercial rations with the addition of fermented duckweed baker's yeast (Saccaromycese cerevisiae) by 5%, 10%, and 15% respectively. The variables observed were total production cost, receipts, revenue, R/C ratio, BEP units, BEP Price and IOFC. The results of this study showed that the lowest total production cost occurred in P3 treatment of Rp73,027,476.54. The largest acceptance occurred in P0 treatment of Rp85,713,364.00. The largest income between treatments was obtained in P1 treatment amounting to Rp 7,144,699.46. The lowest BEP Unit was obtained in the P3 treatment of 3,436.95 kg, while the lowest BEP Price occurred in the P1 treatment of Rp19,187.20. The highest R/C ratio was obtained by the P1 treatment of 1.094. The largest IOFC was obtained in the P1 treatment of Rp25,970,366.46. From the results of this study it can be concluded that broilers in the finisher phase given rations with the addition of 5% duckweed (Lemna. sp) fermented baker's yeast (Saccharomyces cerevisiae) were able to increase revenue, R/C ratio, and IOFC by decreasing total production costs, BEP Units, and BEP Prices.cc